Peran total quality management dan manajemen reward terhadap kinerja guru melalui komitmen kerja pada sekolah dasar Kecamatan Jombang Kota Cilegon - Raman, Raman; Yusuf, Furtasan Ali; Hayadi, Herawan; Suparmoko, Muhamad; Sari, Gema Ika; Prasetyo, Eko (Universitas Muhammadiyah Magelang, 2024)
Total Quality Management (TQM), a comprehensive quality management approach, has been proven to increase efficiency and effectiveness in various sectors, including education. However, its implementation in elementary schools, especially in Cilegon City, is often not optimal. This problem will affect TQM on teacher performance through work commitment and reward management systems in these schools. This shows that there is a gap between the expected implementation of TQM and the existing reality, where many schools have not fully adopted or integrated TQM principles in daily operations. There are still many schools that have not implemented TQM effectively, often facing problems in inconsistent learning standards and school management. This research aims to analyze the influence of Total Quality Management (TQM) and Management Reward on teacher performance with work commitment as an intervening variable in elementary schools in Jombang District, Cilegon City. In the educational context, the application of TQM principles is important to ensure continuous improvement in the quality of education. On the other hand, Management Rewards play a role in motivating and appreciating teachers so that they can improve their performance. This research uses a quantitative approach with a survey method, involving a number of elementary school teachers as respondents. The data obtained was analyzed using the Structural Equation Modeling (SEM) technique to test the relationship between the variables studied. The research results show that the implementation of TQM and Management Reward has a positive and significant influence on teacher performance. Work commitment was found to be an intervening variable that strengthens the influence of TQM and Management Reward on teacher performance. These findings emphasize that to achieve optimal teacher performance, integration between quality and reward management strategies is needed, as well as strengthening teacher work commitment. The practical implication of this research is that it is important for school policy makers to implement TQM and an effective reward system to increase teacher commitment and overall performance